Randomised study comparing 48 and 96 weeks peginterferon α-2a therapy in genotype D HBeAg-negative chronic hepatitis B. Issue 2 (2nd August 2012) - Lampertico, Pietro; Viganò, Mauro; Di Costanzo, Giovan Giuseppe; Sagnelli, Evangelista; Fasano, Massimo; Di Marco, Vito; Boninsegna, Sara; Farci, Patrizia; Fargion, Silvia; Giuberti, Tiziana; Iannacone, Claudio; Regep, Loredana; et al.
Abstract : Objective: Treatment with peginterferon α-2a (PegIFN) for 48 weeks is the standard of care for selected HBeAg-negative patients chronically infected with hepatitis B virus (HBV), but with limited treatment efficacy. A study was undertaken to investigate whether treatment extension to 96 weeks improves the outcome in this patient population. Methods: 128 HBeAg-negative patients (120 genotype D) were randomised to weekly 180 μg PegIFN for 48 weeks (group A, n=51), 180 μg PegIFN for 48 weeks followed by 135 μg weekly for an additional 48 weeks (group B, n=52) or 180 μg PegIFN plus lamivudine (100 mg/day) for 48 weeks then 135 μg PegIFN for 48 weeks (group C, n=25). Endpoints were alanine aminotransferase normalisation plus HBV DNA <3400 IU/ml (primary), HBV DNA <2000 IU/ml and HBsAg clearance at 48 weeks after treatment. Results: Forty-eight weeks after treatment, six patients in group A and 13 in group B achieved alanine aminotransferase normalisation plus HBV DNA <3400 IU/ml (11.8% vs 25.0%, p=0.08), 6 vs 15 patients had HBV DNA <2000 IU/ml (11.8% vs 28.8%, p=0.03), 0 vs 3 achieved HBsAg clearance (0% vs 5.8%, p=0.24) and 0 vs 5 had HBsAg <10 IU/ml (0% vs 9.6%, p=0.06). While extended PegIFN treatment was the strongest independent predictor of response, the combination with lamivudine did not improve responses. Discontinuation rates were similar among the groups (19.6%, 23.1%, 32.0%, p=0.81) and were mostly due to PegIFN-related adverse events. Conclusions: In HBeAg-negative genotype D patients with chronic hepatitis B, PegIFN treatment for 96 weeks was well tolerated and the post-treatment virological response improved significantly compared with 48 weeks of treatment. Trial registration number: http://ClinicalTrials.gov registration number: NCT01095835 .